Seqüência Ordovício-Siluriana e Devoniana no Flanco Norte da Bacia do Paraná - De Alvarenga, Carlos J. S.; Guimarães, Edi M.; Assine, Mario L. [UNESP]; De J. Perinotto, J. Alexandre [UNESP]; Laranjeira, Nina P. F. (My University, 1998)
Two stratigraphic sequences characterize the basal units of the Paraná basin. The Ordovician-Silurian sequence overlie directly the Neoproterozoic basement and consists of a 55m-thick unit of coarse-grained sandstones, diamictites, fossiliferous shales and fine-grained micaceous sandstones. The Alto Garças Formation constitutes the base of the sequence and is made of coarse-grained, massive and reddish sandstones associated with conglomeratic lenses. Diamictites with pebbles of diverse composition in siltic and arenaceous matrix were deposited during the Ordovician-Silurian glaciation. Whenever the basal sandstones are absent, the diamictites directly overlie the basement. The diamictites were previously included in the Vila Maria Formation. However our study revealed that they are part of the Iapó Formation. A transgressive event following the glaciation is marked by the deposition of the Vila Maria Formation, which is characterized by fossiliferous (mollusks, brachiopods, cryptospores and microplankton) and laminated shales and siltstones, grading upward to fine-grained micaceous sandstones with hummocky cross stratification. Layers containing trace fossils (Anthrophycus) occur at the transition between the siltstones and the sandstones. The Devonian sequence is represented by 80-170 meters thick sandstones of the Furnas Formation (lower unit) and a sucession of sandstones, siltstones and shales of the Ponta Grossa Formation (upper unit). Unlike other areas of the Paraná Basin, the Ponta Grossa Formation is characterized by coarsening-upward succession beginning with fine sandstones and grading upward to coarse and very-coarse sandstone beds. Cretaceous modifying tectonics affected the Paleozoic sequences, which are cut by a series of faults, in some cases showing displacements greater than 500 meters.
Keywords: Devonian; Paraná Basin; Silurian; Stratigraphy